A Facile and Versatile Synthesis of Energetic Furazan‐Functionalized 5‐Nitroimino‐1, 2, 4‐Triazoles. Issue 21 (18th April 2017) - Xu, Zhen; Cheng, Guangbin; Yang, Hongwei; Ju, Xuehai; Yin, Ping; Zhang, Jiaheng; Shreeve, Jean'ne M.
Abstract: An analogue‐oriented synthetic route for the formulation of furazan‐functionalized 5‐nitroimino‐1, 2, 4‐triazoles has been explored. The process was found to be straightforward, high yielding, and highly efficient, and scalable. Nine compounds were synthesized and the physicochemical and energetic properties, including density, thermal stability, and sensitivity, were investigated, as well as the energetic performance (e.g., detonation velocities and detonation pressures) as evaluated by using EXPLO5 code. Among the new materials, compounds4 –6 and11 possess high densities, acceptable sensitivities, and good detonation performances, and thereby demonstrate the potential applications as new secondary explosives. Abstract : High energy : An analogue‐oriented synthetic route for the formulation the title compounds was developed. The process was found to be straightforward, high yielding, and highly efficient, and scalable for the synthesis of high‐performance energetic materials.